REINTERPRETASI HADIS MAYAT DIAZAB ATAS TANGISAN KELUARGANYA DENGAN HERMENEUTIKA PAUL RICOEUR - Sa'dudin, Ihsan; Siregar, Muhammad Nasrun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Islam as the religion of raḥmah li al-‘âlamin has the dimension of law-setting based on the conditions of time and place of law will be determined. The law that Rasulullah set in a ḥadîth is inseparable from geographical, sociological, and historical conditions lied behind it. The dynamics of interpretation science help the reinterpretation of a ḥadith to produce a law that is actual and in accordance with the conditions but not out of the rules of Qur’an, because Qur’an indeed is as the main legal source in Islam. This paper is to describe the interpretation of the ḥadîth about the corpse being tortured by the tears of his family (Muslim 1536) with Paul Ricoeur's interpretation approach. Author comes to the conclution that the use of the word bukâ’ in the matan of ḥadîth means corpse actually got tortured because of the hysterical cry of his family who bemoaned over it. As for the historical aspects of this ḥadîth when Rasulullah saw the Jews weep for his family who died with hysterical cry. Thus, the point of emphasis of the ḥadîth is a way of responding those who grieve. If the attitude is excessive until hysterical wailing for days, then it includes an inappropriate attitude that is not even recommended in the Qur'an.